Ablation of paroxysmal and persistent atrial fibrillation in the very elderly real‐world data on safety and efficacy. Issue 12 (19th October 2020) - Willy, Kevin; Wasmer, Kristina; Dechering, Dirk G.; Köbe, Julia; Lange, Philipp S.; Bögeholz, Nils; Ellermann, Christian; Reinke, Florian; Frommeyer, Gerrit; Eckardt, Lars
Abstract: Background: The role and technique of catheter ablation of atrial fibrillation (AF) in the elderly is unclear. While in young patients pulmonary vein isolation (PVI) has evolved as first option, in older patients decision is often made in favor of drugs as higher complication rates and less benefit are suspected. Therefore, data on PVI of paroxysmal and persistent AF in these patients is still sparse but of eminent importance. Hypothesis: PVI is comparably safe in the very elderly with similar recurrence and complication rates. Methods: We enrolled all patients (n = 146) aged >75 years who underwent a first PVI over a period of 10 years (2009‐2019) from our prospective single‐center ablation registry. Mean follow‐up time was 231 ± 399 days. Results: Acute ablation success defined as complete PVI and sinus rhythm at the end of the ablation procedure was high (99%). Severe periprocedural complications occurred in 3.3% (stroke/TIA n = 2; 1.3%; pericardial effusion n = 3; 2%). In 4.6% of patients symptomatic sick‐sinus‐syndrome was unmasked after PVI resulting in pacemaker implantation. There were no deaths related to PVI. Recurrence rate of symptomatic AF was 37.3% resulting in a Re‐PVI and/or substrate ablation in 32 pts (20.9%). During follow‐up pacemaker implantation plus atrioventricular node ablation was performed in 10 pts (6.8%). There was a trend toward lower recurrence rates with single‐shot devices (cryoballoon, multielectrode phased‐radiofrequency ablation catheter) than with point‐by‐point radiofrequency while complication rates did not differ. Conclusion: PVI for AF is a feasible treatment option also in patients >75 years with a reasonable success and safety profile. Higher success rates occurred in patients treated with a single‐shot device as compared to point‐by‐point ablation.